2014
DOI: 10.1088/1367-2630/16/10/105002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neighboring cells on the stiffness of cancerous and non-cancerous human mammary epithelial cells

Abstract: Using an Atomic Force Microscope (AFM) with a 5.3 μm diameter spherical probe, we determined mechanical properties of individual human mammary epithelial cells. The cells were derived from a pair of cell lines that mimic cell progression through four phases of neoplastic transformation: normal (nontransformed), immortal, tumorigenic, and metastatic. Measurements on cells in all four phases were taken over both the cytoplasmic and nuclear regions. Moreover, the measurements were made for cells in different micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 62 publications
(104 reference statements)
4
47
1
Order By: Relevance
“…While our MSDs are comparable to MSDs previously determined by particle-tracking experiments in breast cells, our values of G are several orders of magnitude smaller than measurements by AFM indentation (500–2000 Pa) even on the same cell types (Li et al 2009; Lee et al 2012; Network TPS-OC 2013; Guo et al 2014b). The discrepancy probably arises because these techniques probe distinct structures within the cell.…”
Section: Discussionsupporting
confidence: 78%
“…While our MSDs are comparable to MSDs previously determined by particle-tracking experiments in breast cells, our values of G are several orders of magnitude smaller than measurements by AFM indentation (500–2000 Pa) even on the same cell types (Li et al 2009; Lee et al 2012; Network TPS-OC 2013; Guo et al 2014b). The discrepancy probably arises because these techniques probe distinct structures within the cell.…”
Section: Discussionsupporting
confidence: 78%
“…Recent experimental evidence [15][16][17][18] have revealed that tumor cells exhibit a broad distribution of various biomechanical properties. These include intra-tumor heterogeneity in cell stiffnesses [17,[19][20][21][22], stresses, and cell-cell interactions [21,23]. However, there is no consensus on how these heterogeneities affect the mechanical behavior at the tissue level.…”
mentioning
confidence: 99%
“…For example, the tumor microenvironment is composed of blood and lymphatic vessels and a variety of nonmalignant host cells, including fibroblasts, monocytes, macrophages, mast cells, mesenchymal stem cells and so on [89], [90]. Recent studies have shown that cell-cell contacts have a significant effect on cell mechanics [91]- [93]. In 2014, Guo et al [91] applied AFM to investigate the mechanical properties of cells in three different microenvironments as related to cell-cell contacts, including isolated cells, cells residing on the periphery of a contiguous cell monolayer, and cells on the inside of a contiguous cell monolayer.…”
Section: Cell-cell Contactmentioning
confidence: 99%
“…Recent studies have shown that cell-cell contacts have a significant effect on cell mechanics [91]- [93]. In 2014, Guo et al [91] applied AFM to investigate the mechanical properties of cells in three different microenvironments as related to cell-cell contacts, including isolated cells, cells residing on the periphery of a contiguous cell monolayer, and cells on the inside of a contiguous cell monolayer. The results showed that the stiffness of cancer cells was less sensitive to the microenvironment than normal cells.…”
Section: Cell-cell Contactmentioning
confidence: 99%